Pengaruh Inflasi Terhadap Pertumbuhan Ekonomi di Pematang siantar Tahun 2015-2020 - Bosman Firdaus Hutauruk; Binsar Tison Gultom; Anton Luvi Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The results of this research state that: 1) The influence of inflation on economic growth is positive. If inflation increases by 1, then economic growth is 0.338. 2) The value of tcount > ttable, then Ha is accepted and H0 is rejected. Thus, there is a significant influence of inflation on economic growth in Pematang Siantar 2015-2020. 3). If inflation increases, economic growth in Pematang Siantar will increase. Where, the magnitude of the influence of inflation on economic growth in Pematang Siantar in 2015-2020 was 20.5%.